Sharia Performance Ratio Factor: What is the Deposit Financing Ratio and Financing Quality? - Utami, Anita Dwi; Apriani, Peni; Nuryanti, Nuryanti; Maharani, Asyifa Ayu (Baca Dulu Publisher, 2024)
Islamic banking is the largest sector in the Islamic financial industry. Financial performance refers to the ability to earn income, carry out financial responsibilities, and achieve other goals. Good performance increases customer trust and is very profitable for banks. One of the good performances to increase public trust is through good Islamic financial performance values with the IPR ratio. One of the factors that affect the value of Islamic financial performance is FDR and NPF. The higher the FDR, the better the IPR because the bank optimizes its performance. The higher the NPF value, the worse the IPR because the bank is considered less good at managing problematic financing. The analysis of the research data used panel data regression analysis. The research sample was 12 Islamic banks in Indonesia with a time period of 2019 and 2023. The results showed that FDR had no significant effect on IPR. NPF had a significant negative effect on IPR. The implication of this study is that the NPF ratio which takes into account problematic financing can affect Islamic Bank Performance, especially in terms of Islamic Performance. Islamic Banks are expected to pay more attention to their financial performance.